PENGEMBANGAN MODEL PENDIDIKAN MULTIKULTUR PADA SEKOLAH MENENGAH ATAS DI KAWASAN PANTAI PROVINSI LAMPUNG - Sudirman AM; Karwono Karwono; Juhri AM (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2016)
The objective of research to set up curriculum development about multicultural education at school beach area through identification and need assessment analysis. So can be formula competence of multicultural education, instructional analysis subordinate to easy in learning, and the result of identification attitude the student as generally characteristic can be used as approach strategy in learning appropriate multicultural characteristic of the student. Used of the method in this research Model of Development Instructional System Curriculum 1975 as a parameter after process interaction in learning. In instructional considered (1) knowledge of the student, (2) needed material in learning, (3) what will to do in his activity, (4) methods and what material needed for innovation attitude of the student considered the goal of learning education. In this research used model development in learning Walter Dick & Loe Carey, and model approach system. After need analysis assessment treated, to description and classification of concept multicultural education: basic concept of ethnic, spiel effect of ethnic justness and religion, and an ideal of learning education. Based on analysis above there are conclusion (1) identification of need assessment multicultural education by identification competency from stakeholder education and curriculum regional as specify multicultural education; (2) the result identification competence multicultural education at high school grouped in system religion, organisation, knowledge, language, art, source of life, technology, and accessories. (3) The analysis characteristic multicultural education grouped competency multicultural education in the region of attitude, intellectual, cognitive strategy, and verbal information.